Analisis Kronopotensiometri Arus Balik pada Interaksi Elektrokimia Platina-Xantat - Arief Sudarsono (Institute for Research and Community Services (LPPM) ITB, 1988)
The electrochemical interaction of xanthate ions commonly used as a sulphide minerals flotation collector with platinum electrodes is analyzed by using chronopotentiometric methods. Currents were applied to a platinum electrode immersed in xanthate free and xanthate containing borate solutions. The formation of dixanthogen from xanthate ions oxidation was observed at the application of positive currents. Its reduction is observed at negative currents. The equilibrium of xanthate-dixanthogen couple is applied current dependent. At low applied currents, the time required to reach the equilibrium is longer than the one of high applied currents. Interaksie letrokimia antara xantat sebagai reagen flotasi dengan logam platina dipelajari dengan cara pemuatan berganti. Pemuatan dilakukan dengan memberikan arus pada elektroda platina yang tercelup dalam larutan xantat dengan berbagai konsentrasi. Oksidasi ion xantat menjadi dixantogen teramati beberapa saat setelah pemberian arus positif dan reduksi dixantogen terjadi beberapa saat setelah pemberian arus negatif. Tercapainya kesetimbangan antara ion xantat dengan dixantogen sangat bergantung pada kuat arus yang diberikan. Pada kuat arus yang rendah diperlukan waktu yang relatif lebih lama untuk mencapai kesetimbangan.